A compressive sensing algorithm for hardware trojan detection - priyatharishini m; M. Nirmala Devi (Institute of Advanced Engineering and Science, 2019)
Traditionally many fabless companies outsource the fabrication of IC design to the foundries, which may not be trusted always. In order to ensure trusted IC’s it is more significant to develop an efficient technique that detects the presence of hardware Trojan. This malicious insertion causes the logic variation in the nets or leaks some sensitive information from the chip, which reduces the reliability of the system. The conventional testing algorithm for generating test vectors reduces the detection sensitivity due to high process variations. In this work, we present a compressive sensing approach, which can significantly generate optimal test patterns compared to the ATPG vectors. This approach maximizes the probability of Trojan circuit activation, with a high level of Trojan detection rate. The side channel analysis such as power signatures are measured at different time stamps to isolate the Trojan effects. The effect of process noise is minimized by this power profile comparison approach, which provides high detection sensitivity for varying Trojan size and eliminates the requirement of golden chip. The proposed test generation approach is validated on ISCAS benchmark circuits, which achieves Trojan detection coverage on an average of 88.6% reduction in test length when compared to random pattern.